A simplified model to assess vulnerable areas for urban regeneration. (April 2019) - Ruá, María José; Huedo, Patricia; Civera, Vicent; Agost-Felip, Raquel
Highlights: It is challenging to standardize a model for urban sustainability assessment. This work presents a simplified method, focusing on vulnerable areas in a city. An expert-led process is performed assisted by participatory processes. It permits the assessment within the timeframe required for the decision making. Abstract: The plethora of approaches to assess urban sustainability entails the challenge of selecting the most appropriate model. Theoretical models constitute a necessary and valuable starting point, but here we highlight the limits of their practical implementation. We develop a simplified model that permits the attainability and applicability to actual cases by focussing on vulnerable urban areas, based on the selection of ad hoc indicators. The latter implies performing an in-depth analysis of the physical and socio-economic context due to the variety of urban models. Afterwards, an expert-led process is carried out to select appropriate indicators by considering people's discourse through participatory techniques, especially the vulnerable population's interests. This, together with information availability, determines the final model. The applicability of the model was tested and actually applied to the development of the new Land-Use Plan of Castellón (Spain), and to define and evaluate vulnerable areas that need to be prioritised in potential urban interventions. The indicators permit a vulnerability assessment within the time frame required for decision making on the priority interventions in certain urban land planning areas. As a result, 17 areas were defined, analysed and compared.